El datum geodesic de Ocotepeque y el datum satelitario del sistema WGS84. - Dörries, Esteban; Roldán Rodríguez, Julio Roberto (Uniciencia, 2004)
At present, in Costa Rica two coordinate systems are in use. The Lambert coordinate system by the National Geographic Institute, defined within the Ocotepeque’s datum, and the CRTM by the National Cadastre, defined from the GPS satellite datum. In order to establish the scientific basis and proper techniques to produce recommendations that allowed to establish norms aiming at the unification of the reference system and ambiguities a research project was executed by the School of Land surveying, Cadastre and Geodesia of the Universidad Nacional called “Comparative Study of the Ocotepeque Geodetic datum and the WGS84 System Satellite Datum”. The general objective of the project was to perform a comparative study of the National Geodetic Network used by the National Geographic Institute, formed by triangulated chains, base of the national and official cartography, and oriented in relation to the Ocotepeque´s geodetic datum, and a network obtained by GPS measurements by the National Cadastre and the Universidad Nacional as partial networks, formed by figures and oriented within the WGS84 satellite datum.